Green tea extract attenuates MNU-induced photoreceptor cell apoptosis via suppression of heme oxygenase-1 - Emoto, Yuko (J Toxicol Pathol, 2015)
The effects of green tea extract (GTE) on N-methyl-N-nitrosourea (MNU)-induced photoreceptor cell apoptosis were examined, and the possible mechanisms of action of GTE were assessed. Alterations in the retinal morphological architecture were determined by hematoxylin-eosin staining, vimentin immunoreactivity, and photoreceptor cell apoptosis (TUNEL labeling). Expression of oxidant marker, heme oxygenase (HO)-1, mRNA levels in outer nuclear cells was assessed by laser capture microdissection (LCM). Sprague-Dawley rats were given 40 mg/kg MNU at 7 weeks of age in the absence and presence of 250 mg/kg GTE treatment (once daily from 3 days prior to MNU for a maximum 10 days). Although photoreceptor cell degeneration began 24 hr after MNU, the morphological effects of GTE at the time point were not definitive. However, GTE lowered TUNEL labeling and HO-1 mRNA expression. At 7 days after MNU, photoreceptor damage was attenuated by GTE treatment. Therefore, the ability of GTE to reduce MNU-induced photoreceptor cell apoptosis may be due to its antioxidant properties.